O ensino médio politécnico noturno e os jovens estudantes de uma escola da região oeste de Santa Maria/RS: um estudo de caso - Paloma, Rebeca Ramos (2016)
This research is part of the Master s degree in Education at the Federal University of Santa Maria in the Research Field "School Practices and Public Policy" and has presented the following issue: What are the experiences about the Polytechnic High School of young students in a night High School in the western region of Santa Maria/RS? . This research has as a general goal to analyze the experiences on the Polytechnic High School of young students in a night High School of the western region of Santa Maria. The specific goals are: to search the theoretical elements about the theme Polytechnic High School, about the night High Schools and Youth, to identify the youth present in the night High Schools in a Public School of the western region, to verify the experiences of the youth present in the process of the night Polytechnic High School.The elements were analyzed quantitatively and qualitatively through a case study in a public High School in Santa Maria.This appraisal has been made through 53 questionnaires and three focus groups, which has presented information such as gender, marital status, color or race, education, information about the school and the occupational situation of young people, and the multiple experiences of young people in school and in the Polytechnic high school. The discussion was made based on studies of authors such as Melucci (1997), Novaes (2003), Abramo (2005), Abramovay (2015), Azevedo e Reis (2013), Camacho (2014), Carrano (2005), Coorochano (2014), Ramos (2006), Sposito (1999), Dayrell (2014), Tomazetti et al. (2011, 2012), among others. It has been found that the young people have presented multiple experiences in the school environment and in high school. Among these experiences, it is highlighted that the theoretical conceptions of Polytechnic High School have not been experienced as a practice by the young people, the relation between theory and practice ended up occurring in isolated moments of high school.